(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The research aims to identify The role of Digital Literacy in Enhancing Professing Development among Teachers of The First Cycle of Basic Education and Ways to Overcome it in light of the Requirements of The Digital Age. The research followed the descriptive analytical approach, and the research sample reached (338) male and female teachers who were selected by a simple random method from schools. The first episode, in the city of Damascus countryside, applied to them a questionnaire about The role of Digital Literacy in Enhancing Teacher’s Development and the means of overcoming it in in light of the Requirements of The Digital Age(prepared by the researcher) after ensuring its validity and reliability. The results indicated the following: 1- There is a relationship between digital literacy among teachers of The First Cycle of Basic Education and the need to enhance their financial development, and this relationship is confirmed in light of the Requirements of The Digital Age, which allow them to deal with multiple education systems in digital word environment. 2- The need for teachers of basic education to erase their digital illiteracy before providing them with digital knowledge and skills. Which may greatly affect their acceptance of Professing Development programs so that they can benefit from progress scientific and technological to confront it. 3- There are statistically significant differences between the average teachers’ answers to the questionnaire items according to the academic qualification variable. 4- There are statistically significant differences between the average teachers’ answers to the questionnaire items according to the years of experience variable in favor of (5 years and more). 5- There are statistically significant differences between the average teachers’ answers to the questionnaire items according to the gender variable (Male teachers). 6- Among Ways to Overcome it in light of the Requirements of The Digital Age: Establishing general policies and legal legislation that include a mechanism for dealing with digital tools. • Establishing nalional projects digital literacy. • Transforing educational institution into incubating environment for digital technology.